A Modelling of 500 Kv Long Transmission Line and Fault Detection Using Inverse Definite Minimum Time Over Current (IDMT O/C) relay - Noor Fadzilah Mohamed Sharif,; Khairun Neesya Mohamed Shafiee,; Nur Fatin Izzati Tajudin,; Nazatul Shima Moh Nazar, (Penerbit Universiti Kebangsaan Malaysia, 2025)
As electricity demand increases day by day due to economic growth, the process of transmitting efficient electrical power is vital. Thus, a power simulation study is required to determine the mechanism of the transmission line, and possible faults that occurred in the transmission line system. On a daily basis, single line to ground fault (L-G), double line to ground fault (2L-G), and triple line to ground fault (3L-G) are the faults that normally occur in the long transmission line system. In this project, a model of a 300km/500 kV EHV transmission line consisting of a three-phase source, distribution line, and load is simulated using MATLAB software. When the L – G fault is applied, the voltage is diminished to zero and upon fault clearance, the R – G line produced overvoltage and overcurrent by 518.9 kV and 1889 A, which increased about 46.83% and 15.67% compared to normal lines of Y – G and B – G at 353. kV and 1633 A. Then, for the 2L – G fault, again the voltage is reduced to zero and when fault clearance occurred, the R – G and Y – G lines experienced overvoltage and overcurrent at 570.4 kV and 708.5kV, which showed more than 60% transient compared to normal line B-G at 353.4 kV. In Contrast, the 3L – G fault causes all transmission lines to experience overvoltage and overcurrent at different times and can damage the whole transmission system. Thus, to reduce the severe impact of fault, the Inverse Definite Minimum Time Over Current (IDMT O/C) relay protection is installed in the line model.